Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1158/1078-0432.ccr-13-1950
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α of Bone Marrow Endothelial Cells Implies Relapse and Drug Resistance in Patients with Multiple Myeloma and May Act as a Therapeutic Target

Abstract: Purpose: To investigate the role of hypoxia-inducible factor-1a (HIF-1a) in angiogenesis and drug resistance of bone marrow endothelial cells of patients with multiple myeloma.Experimental Design: HIF-1a mRNA and protein were evaluated in patients with multiple myeloma endothelial cells (MMEC) at diagnosis, at relapse after bortezomib-or lenalidomide-based therapies or on refractory phase to these drugs, at remission; in endothelial cells of patients with monoclonal gammapathies of undetermined significance (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 44 publications
2
55
0
Order By: Relevance
“…Therefore, DCE-MRI before the start of therapy might have predictive and prognostic implications. This assumption is supported by a recent study, which demonstrated that proangiogenic factors lead to drug resistance and relapse in patients with multiple myeloma (28).…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, DCE-MRI before the start of therapy might have predictive and prognostic implications. This assumption is supported by a recent study, which demonstrated that proangiogenic factors lead to drug resistance and relapse in patients with multiple myeloma (28).…”
Section: Discussionmentioning
confidence: 61%
“…Gels were silver stained and analyzed on PDQuest software (Bio-Rad; ref. 21). Spots of interest were excised, destained, dehydrated in acetonitrile, and digested with trypsin.…”
Section: Two-dimensional Gel Electrophoresis and Mass Spectrometry Prmentioning
confidence: 99%
“…Indeed, MM endothelial cells (MMEC) play a crucial role in MM progression and HIF-1α protein is reported to be expressed constitutively and activated in MMEC in a well-defined proportion of patients experiencing relapse or refractory to treatment. More importantly, patients with MMEC expressing the HIF-1α protein have shorter overall survival [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Although the pro-angiogenic role of HIF-1α has already been established in MM [15, 16], to our knowledge no studies have documented MMEC adaptive response to hypoxia in terms of survival, apoptosis and/or autophagy. We therefore decided to investigate and compare the effects of hypoxia on bone marrow EC of active multiple myeloma patients and on healthy quiescent EC, namely human umbilical vein EC (HUVEC).…”
Section: Introductionmentioning
confidence: 99%